PELATIHAN KARAWITAN PAKELIRAN WAYANG GEDOG SEBAGAI KEBERTAHANANBUDAYA DI LKP SANGGAR PARIKESIT KABUPATEN SUKOHARJO - Dian Nastiti; Suraji (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This community service initiative was designed to support the regeneration of artists, particularly in the field of Karawitan. The program was executed through a combination of individual and group training sessions, including ensemble practices (tabuh bersama). Training was held twice weekly: one session for small groups and one for large group rehearsals. The repertoire taught consisted of gending-gending pakeliran Wayang Gedog Surakarta such as Ayak, Srepeg, Sampak, and others. Adolescents were selected as the target participants due to their productive age range, making them more receptive to the learning materials. Moreover, young people are considered the key agents in preserving Javanese culture, especially the art of Karawitan.The community service comprised three distinct stages: preparation, implementation, and evaluation. In the preparation phase, the drill method was employed as the primary training approach. As a direct result of this program, the youth Karawitan group from Kotakan Village successfully presented a cohesive wayang kulit performance.